Unpacking the Green Leadership-Environmental Performance Link: The Role of Innovation, GHRM and Environmental Values (Journal of Social Sciences Review, 2025)
The paper investigates connections among green transformational leadership-GTL, environmental performance-EP association along GHRM (Green Human Resource Management) and, Green Innovation-GI as mediating factors. It explores environmental values' moderating role among GTL and EP. Using structural equation modeling, 15 SMEs were surveyed, and 110 data points were collected from individuals. Results indicate that GTL contributes significantly to EP. Additionally, the mediation analysis confirms that GTL and EP are positively mediated by GHRM and GI. It is also highlighted that EV has a moderating effect on GTL/EP relationships. A sustainable business culture can be fostered by utilizing these insights.
Keywords: Leadership; Values; Innovation; Performance; GHRM